Levetiracetam monotherapy for the treatment of infants with epilepsy. (March 2018) - Arican, Pinar; Gencpinar, Pinar; Cavusoglu, Dilek; Olgac Dundar, Nihal
Highlights: Of the 92 patients, 66% were seizure free under levetiracetam monotherapy. The effect of levetiracetam on EEG abnormalities is associated with its effect in control of epileptic seizures. Levetiracetam may show a low incidence of side effect in infant patients. Abstract: Purpose: Levetiracetam is a broad-spectrum anti-epileptic drug that is effective against both focal and generalized epilepsies. In this study, we aimed to evaluate the efficacy, tolerability and safety of levetiracetam monotherapy in the management of different seizure types in children with epilepsy under the age of two. Method: This retrospective study was conducted on children with a diagnosis of epilepsy from January 2014 to January 2017. To be included in the study, patients were required to be less than two years of age at the time levetiracetam was initiated as initial monotherapy and to be followed clinically for at least 6 months. Results: Of the 92 patients, 61 (66%) patients were seizure free. Fifty-eight percent of the patients (31 of 53) with focal epilepsy were seizure free and 77% (30 of 39) generalized epilepsy were seizure free. We found that levetiracetam monotherapy was effective in both focal and generalized epilepsy. Levetiracetam monotherapy was significantly more effective in patients with unknown etiologies (p = 0.004). Seizure freedom rate under levetiracetam monotherapy was significantly higher in patients with normal psychomotor development (p = 0.000). Seizure freedom rate under levetiracetam monotherapy was significantly higher in patients with unknown etiologies and normal psychomotor development. Normal psychomotor development was the strongest predictor of seizure control under levetiracetam monotherapy (OR = 6; 95% CI = 2.3–16.0; p < 0.001). Five children (1%) reported irritability. No hematological or biochemical, or behavioral adverse side effects except irritability were reported in any children. No patient discontinued levetiracetam therapy because of treatment-related side effects. Conclusion: Our study showed levetiracetam to be an effective, well tolerated and safe agent for the treatment of a variety of seizure types and etiologies seen in infants.